Assessing and reducing sources of gene expression variability in Staphylococcus epidermidis biofilms. (December 2014) - Sousa, Cármen; França, Angela; Cerca, Nuno
Gene expression quantification can be a useful tool in studying the properties of bacterial biofilms. Unfortunately, techniques such as RNA extraction, cDNA synthesis, and quantitative PCR (qPCR) can introduce variability into mRNA transcript measurements, obscuring biologically relevant results. Here we sought to identify the steps that impair accurate gene expression quantification from Staphylococcus epidermidis biofilm samples. We devised an experimental setup that could be used to determine the contribution of each experimental step to the variability of mRNA transcript measurement. Among factors tested, biofilm growth contributed the most bias to gene expression quantification. Additional experiments demonstrated that pooling biofilms together reduced this variability, resulting in more accurate gene expression analysis results. We therefore recommend pooling in order to reduce the variability associated with gene expression quantification from biofilm samples.